Model Tests on Y-Shaped Piles under Compressive and Lateral Loading in Saturated Sand - Lian-wei Ren; Quan-wei Yang; Gang-qiang Kong; Zhi-lin Dun; Xin-yu Wang (Geofluids)
Y-shaped piles are a new type of pile whose cross-section is like the letter Y: they are often used in ground improvement for road or train subgrades in the eastern coastal region of China. To investigate the bearing behaviour of Y-shaped piles in saturated sand, a series of model tests under compressive and horizontal load for Y-shaped piles, C1 circular pile (the same cross-sectional area of Y-shaped pile), and C2 circular pile (the same perimeter of Y-shaped pile) were carried out. Comparative analysis was conducted on bearing capacity, axial force and side resistance distribution, load sharing ratio, bending moment, and lateral soil pressure distribution along the embedded length. The results show that the bearing capacity of a Y-shaped pile does not increase in proportion, and the shaft resistance is weakened to some extent in saturated sand; Y-shaped pile can effectively improve the compressive bearing capacity for the same amount of concrete. The lateral bearing capacity of a Y-shaped pile has directionality, and hanging a circular section into a Y-shaped section may improve the horizontal bearing capacity for the same amount concrete, but cannot give full play to the advantage of the larger side area for horizontal bearing capacity in saturated sand.